Pemberdayaan Ibu Hamil dalam Mengenali Kebutuhan Spiritual pada Periode Antenatal - Wahyuni, Sri; Istikhomah, Henik (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: In response to the growing need to integrate spiritual aspects into holistic midwifery care, the outcomes of community service activities serve as a scientific foundation for implementing spiritual interventions during pregnancy. Objective: The purpose of this community service activity was to empower pregnant women in recognizing their spiritual needs. Method: The activity was in the form of training for pregnant women in recognizing the spiritual needs of pregnant women. A total of 20 pregnant women from Joton Village, Jogonalan 2 Klaten Health Center area participated. The activity was carried out from May to September 2024. The implementation of community service activities in the form of providing training to pregnant women, with details of the activities on the first day being training on spiritual needs in pregnant women, in recognizing the spiritual needs of pregnant women (lectures, questions and answers) case studies and demonstrations, the second day was training on the use of instruments, the third day was a simulation and demonstration of identifying the spiritual needs of pregnant women using the Patients Spiritual Needs Assessment Scale, the fourth day was an evaluation of the knowledge of pregnant women in recognizing the spiritual needs of pregnant women by measuring through a posttest via Google form. Pre-test and post-test data were analyzed using a t-test difference test. Result: The results of the community service were obtained as many as (90%) pregnant women of healthy reproductive age, mean + SD 29.55 + 4.442, secondary education (80%), multigravida (60%), housewives (85%) and after TM I-III pregnancy. The average pretest score was 159.9 and posttest 168.55 points, so that there was an increase in the score of 8.65 (p value 0.03). Conclusion: There was an increase in the knowledge of pregnant women in recognizing spiritual needs, so that it can be used as material for spiritual adaptation of pregnant women.